Beyond Rasa Theory: Emotional Complexity and Mixed Affect in The Little Clay Cart - Rawal, Deepak (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
The Little Clay Cart (Mṛcchakaṭika) by Shudraka is one of the fine examples of a Sanskrit drama that does not remain within the boundaries of a traditional Rasa theory, but is rather a dense fabric of emotional moods, the classical sentiments of the aesthetics and social realism. Though the play plays with classic rasas like Shringara (love), Hasya (humor) and Karuna (pathos) it also has morally ambiguous characters representative of various social classes, like the chaste courtesan Vasantasena, the poor Brahmin Charudatta, who are there as supporting characters. This multi-layered affectiveness is magnified by the story being interwoven with romance, political intrigue, moral dilemmas, and social critique, resulting in a more multi-layered experience of affect, contradicting the notion of single dominant rasa. The affective involvement of the audience is also enhanced by structural lawful irregularities of the play, like suspenseous murders, fortune turns, and theft and political intrigues sub plots. The clay cart, which is turned into gold with the jewels of Vasantasena, symbolically reflects the relationship between material and moral values as it is the reflection of sacred and mundane, righteousness and misfortune coexisting in one. Investigating human courage, agency and moral behavior, as well as love, humor, and suffering, Shudraka creates a very emotional and a very familiar picture of a city, which is touching to everyone.